2019
DOI: 10.1111/jocn.14767
|View full text |Cite
|
Sign up to set email alerts
|

Preventive interventions for pressure ulcers in long‐term older people care facilities: A systematic review

Abstract: Aims and objectives To explore the effectiveness of interventions aimed at pressure ulcer (PU) prevention in long‐term older people care facilities (LOPC). Background Pressure ulcers cause suffering for patients and constitute a major financial burden. Although most PUs could be prevented, their number has remained high. To avoid unnecessary suffering and costs, PU prevention must be effective. Design A systematic review. Methods A systematic search was conducted in six electronic databases PubMed (MEDLINE), C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 37 publications
1
26
1
3
Order By: Relevance
“…In LOPC facilities, the incidence and prevalence of PUs have been reduced with PU prevention bundles or programmes (15,37‐38). A review (39) concluded that one third of the PU prevention interventions used in LOPC facilities were reported as effective. However, recent studies have stated that not only PU rates should be reported as an outcome of the intervention, but also compliance of the PU prevention bundle.…”
Section: Introductionmentioning
confidence: 99%
“…In LOPC facilities, the incidence and prevalence of PUs have been reduced with PU prevention bundles or programmes (15,37‐38). A review (39) concluded that one third of the PU prevention interventions used in LOPC facilities were reported as effective. However, recent studies have stated that not only PU rates should be reported as an outcome of the intervention, but also compliance of the PU prevention bundle.…”
Section: Introductionmentioning
confidence: 99%
“…정 등의 간호행위나 의사결정지원 시스템과 같은 다양한 욕창예방간 호수행 프로그램 적용이 효과적인 것으로 보고되었다 [5,6] [16]. 욕창예방간호는 개인의 간호행위뿐만 아 니라 조직역할 수행의 체계적 측면에 영향을 받는다 [3,6].…”
unclassified
“…Dermatological complications may, indeed, be present in SCI, and some of them are life-threatening and need prevention and long-term care. [2,12,15,[23][24][25] The harvested skin biopsies were not exposed to compression ischemia/hypoxia, but only to the general neurovegetative dysfunction of the leg circulation related to SCI and to a wheel-chair life style. Although a group of control normal adult skin biopsies were not available, our humble opinion is that the skin of SCI persons enrolled during the first year after trauma, may be taken as almost normal skin samples (or certainly the less exposed to atrophic changes).…”
Section: Discussionmentioning
confidence: 99%